#### Question

If `y=sqrt(sinx+sqrt(sinx+sqrt(sinx+..... oo))),` then show that `dy/dx=cosx/(2y-1)`

clickto share

#### Solution

`y=sqrt(sinx+sqrt(sinx+sqrt(sinx+..... oo)))`

Let `y=sqrt(sinx+y)`

`y^2=sinx+y `

Differentiat ing w.r.t.x,

`2y.dy/dx=cosx+dy/dx`

`dy/dx=cosx/(2y-1)`

Is there an error in this question or solution?

#### APPEARS IN

#### Related QuestionsVIEW ALL [14]

#### Reference Material

Solution for question: If y=√(sinx+√(sinx+√(sinx+.....∞ ))), then show that dy/dx=cosx/(2y-1) concept: null - General and Particular Solutions of a Differential Equation. For the courses HSC Science (Computer Science), HSC Science (General) , HSC Arts, HSC Science (Electronics)